2009
DOI: 10.1093/schbul/sbn149
|View full text |Cite
|
Sign up to set email alerts
|

Brain-Performance Correlates of Working Memory Retrieval in Schizophrenia: A Cognitive Modeling Approach

Abstract: Correlations of cognitive functioning with brain activation during a sternberg item recognition paradigm (SIRP) were investigated in patients with schizophrenia and in healthy controls studied at 8 sites. To measure memory scanning times, 4 response time models were fit to SIRP data. The best fitting model assumed exhaustive serial memory scanning followed by self-terminating memory search and involved one intercept parameter to represent SIRP processes not contributing directly to memory scanning. Patients di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
25
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(27 citation statements)
references
References 42 publications
2
25
0
Order By: Relevance
“…Additionally, significantly shorter RTs were obtained for the positive probes compared with the negative probes. Faster RTs to positive than to negative probes were reported in several earlier working memory studies with Sternberg paradigm (Pelosi et al, 1995(Pelosi et al, , 1998Brown et al, 2009), while a study reported no RT difference between them (Pratt et al, 1989). Since the original study by Sternberg (1966), several cognitive models were proposed for search strategies on the basis of slopes of RTs to positive and negative probes, such as serialexhaustive search, serial-self terminating search or parallel search with limited capacity (Townsend and Fifić, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, significantly shorter RTs were obtained for the positive probes compared with the negative probes. Faster RTs to positive than to negative probes were reported in several earlier working memory studies with Sternberg paradigm (Pelosi et al, 1995(Pelosi et al, , 1998Brown et al, 2009), while a study reported no RT difference between them (Pratt et al, 1989). Since the original study by Sternberg (1966), several cognitive models were proposed for search strategies on the basis of slopes of RTs to positive and negative probes, such as serialexhaustive search, serial-self terminating search or parallel search with limited capacity (Townsend and Fifić, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…4) was composed of six blocks of memory items separated by fixation blocks (Brown et al, 2009). During a run, two memory sets for each memory set size were presented twice.…”
Section: Methodsmentioning
confidence: 99%
“…Although patients with schizophrenia (SZ) exhibit performance deficits in nearly all aspects of brain function, WM has been identified as one most severely affected functional domains (Bilder, 2009). The neural correlates of WM have been extensively studied using the psychometric and neuroimaging data gathered from healthy adults and from patients suffering from schizophrenia or schizoaffective disorder while performing a variant of the Sternberg Item Recognition Paradigm (SIRP) (Brown et al, 2009). The task involved the presentation of a memory set that included 1, 3, or 5 digits followed by 14 probe digits.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations